Sob as chamas do pentecoste: o mover do pentecostalismo tradicional na assembleia de Deus madureira em Sergipe. - Santos, José Horimo Medeiros dos (2009)
The objective of this work is to analyze the maintenance of the traditional Pentecostal in the church Assemblies of God Church Ministry of Madureira in Sergipe. Since 1980, an assembleinen group already met in Sergipe, denominated Ministry of Madureira, under the leadership of Pastor Jonas Teles da Silva and, in the course of time, it was spreading, now there is more than 70 dispersed temples in the state of Sergipe. The traditional pentecostal, constantly reaffirmed by these religious persons when they refer to the leadership of Rev. Jonas Teles and his objections in relation to the innovations of a possible future has been the subject of ongoing concern within the group. However, the center of the religious world of the faithful ADMM is to reaffirm their way of being all other forms of religious expression, that is, say the following "sound doctrine", the traditional Pentecostalism. Thus, distinguishing the traditional manifestations of spiritual gifts of the current innovation is only possible from the moment that separates the world community of people living a shared religion, a religious individualist consumer society. Hence, when examining the eyes of the religious over the world and life, social representations they use to interpret their own standards within the context of Pentecostalism, we noted the struggle of those who chose to live in the flames of Pentecost.